Rentilly castle on old postcard - Auteur inconnu (Wikimedia Commons, 1910)
Carte postale ancienne issue de Wikimedia Commons. Titre: Rentilly castle on old postcard. The old burned castle of Rentilly (August 21, 1944) now disappeared (Seine-et-Marne, France).
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; Château; Carte postale